Coercion or collaboration: service-user experiences of risk management in hospital and a trauma-informed crisis house. Issue 2 (3rd April 2021) - Prytherch, Hannah; Cooke, Anne; Marsh, Ian
ABSTRACT: Background and aims. Improving care for people in crisis remains high on the UK government agenda. Trauma-informed approaches (TIAs) have been advocated to address concerns raised about psychiatric hospital services by service-users, particularly around the use of coercion in risk management. This study explores service-users' experiences of risk management in both hospital services and a trauma-informed crisis house. Methods. Eight women were interviewed using a semi-structured interview schedule. Interviews were transcribed and analysed using thematic analysis within a critical realist framework. Results and discussion. Four themes were developed. In the first two ('The Medical-Custodial Approach: They Only Think About Physical Safety' and 'Coercion is Counterproductive') participants described hospital as being dominated by a medical-custodial approach, which they said was ineffective in managing long term safety and could exacerbate distress. In the next two themes ('Talking Heals' and 'Relationships as Risk Management') the crisis house was described as using a relational approach to risk management that enabled women to maintain some freedom, privacy and control and was felt to be more effective long term. This research was carried out with a small sample and both recruitment and context likely privileged positive accounts of TIAs. Clinical implications and areas for further research are discussed.